Model Penyelesaian Hutang Anggota Koperasi Terdampak Covid-19 Berbasis Zakat dan Pemberdayaan Produktif - Nur Fadlan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The Covid-19 pandemic has weakened the business sustainability of members of Islamic cooperatives and significantly increased non-performing financing, particularly among micro-entrepreneurs. Meanwhile, conventional debt restructuring mechanisms tend to prioritize institutional financial recovery and often fail to restore members’ productive capacity and dignity. This article examines a debt resolution model for Islamic cooperative members affected by Covid-19 through the utilization of zakat funds based on a productive gharimin approach integrated with sustainable economic empowerment programs. This study employs a qualitative descriptive method using a case study approach involving Islamic cooperatives and zakat management institutions (LAZ), with data collected through interviews, documentation, and observation. The findings indicate that zakat-based debt settlement accompanied by productive empowerment initiatives—such as goat farming, tempeh production, and participation in providing community business infrastructure (MBG)—effectively restores cooperative financial health, reduces non-performing financing risks, and preserves members’ dignity without stigmatization. Furthermore, the cooperative–LAZ synergy model facilitates the transformation of members from financially distressed individuals into empowered and self-reliant economic actors. This model is considered more equitable, humane, and sustainable than conventional debt restructuring and is highly relevant as an Islamic social finance practice for post-pandemic economic recovery.